STRATEGIC DIRECTIONS OF IMPROVING THE TOOL OF STATE REGULATION AND SUPERVISION FOR THE MARKET OF NON-BANK FINANCIAL SERVICES OF UKRAINE - Левченко , Валентина (Socio-economic relations in the digital society, 2019)
The tools of state regulation, supervision, and control over financial intermediaries in Ukraine are analyzed. A generalization of the problems of the development of insurance companies, non-state pension funds and credit unions in Ukraine is made. The strategic principles for improving the tools of state regulation and supervision of the market of non-bank fi nancial services of Ukraine are formed. The expected results from the implementation of the proposed instruments of state influence are determined. Th e system of regulatory and supervisory bodies and instruments, which provided the complex operation will ensure the continuous development of the market in the market of non-bank fi nancial services of Ukraine is formalized. The requirements for regulation and supervision of the non-banking fi nancial services market, which will stimulate the eff ective activity of insurance companies, credit unions, and non-state pension funds, are established.
Keywords: government regulation; non-bank financial services market; insurance companies; credit unions; nonstate pension funds